2019
DOI: 10.1111/cas.14009
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA TPT1‐AS1 promotes tumorigenesis and metastasis in epithelial ovarian cancer by inducing TPT1 expression

Abstract: Increasing numbers of studies have confirmed that long noncoding RNA (lnc RNA ) play a critical role in epithelial ovarian cancer ( EOC ) progression. However, the potential function of the lnc RNA tumor protein translationally controlled 1 ( TPT 1) antisense RNA 1 ( TPT 1‐ AS 1) in EOC is unclear. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 47 publications
(82 reference statements)
6
40
0
Order By: Relevance
“…These findings indicated that TPT1-AS1 may participate as an oncogene in the pathogenesis of GC. Consistently, TPT1-AS1 was remarkably elevated in cervical cancer [18] and ovarian cancer tissues [19]. Moreover, elevated TPT1-AS1 expression predicted worse prognosis in ovarian cancer patients [19].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These findings indicated that TPT1-AS1 may participate as an oncogene in the pathogenesis of GC. Consistently, TPT1-AS1 was remarkably elevated in cervical cancer [18] and ovarian cancer tissues [19]. Moreover, elevated TPT1-AS1 expression predicted worse prognosis in ovarian cancer patients [19].…”
Section: Discussionmentioning
confidence: 67%
“…Consistently, TPT1-AS1 was remarkably elevated in cervical cancer [18] and ovarian cancer tissues [19]. Moreover, elevated TPT1-AS1 expression predicted worse prognosis in ovarian cancer patients [19]. On the contrary, TPT1-AS1 was found to be decreased and identified as a protective lncRNA in glioblastoma [22].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, studies have been done to increase the expression of TPT1-AS1 gene, for example, in 2017, Jiang et al studied cervical cancer both in vivo and in vitro, and observed that lncRNA TPT1-AS1 could be involved as an oncogenic agent in the development of cervical cancer, and also, they introduced it as an effective therapeutic goal [9]. In addition, in 2019, Wu et al studied epithelial ovarian cancer, and observed that lncRNA TPT1-AS1 could lead to tumorigenesis and metastasis in epithelial ovarian cancer [24].…”
Section: Discussionmentioning
confidence: 99%